Critical Realist Methodology Guiding Theory Development: The Case of the Norwegian Second Home Ownership Paradox. Issue 2 (14th March 2016) - Steffansen, Rasmus
Abstract : Informed by a critical realist approach, this article criticizes the dearth of research on the question of the need for capital that prospective owners of modern Norwegian second homes are faced with. The main method used for theorizing capital need is the model for an applied explanatory science proposed by Bhaskar, the RRREIC schema, which helps us understand the necessary components of a second home transaction. This leads to an in-depth analysis of this phenomenon and specifically traces the mechanisms related to and activated by obtaining a bank loan. Through this a paradox arises and doubt is cast on the sustainability of a loan-based second home ownership. Besides uncovering this paradox, the article concludes that a research approach such as the RRREIC schema can provide expanded understanding of the mechanisms involved in Norwegian second home ownership.